Treated HIV Infection and Progression of Carotid Atherosclerosis in Rural Uganda: A Prospective Observational Cohort Study - Siedner, Mark J.; Bibangambah, Prossy; Kim, June-Ho; Lankowski, Alexander; Chang, Jonathan L.; Yang, Isabelle T.; Kwon, Douglas S.; North, Crystal M.; Triant, Virginia A.; Longenecker, Christopher; Ghoshhajra, Brian; Peck, Robert N.; et al. (Journal of the American Heart Association, 2021)
Although ≈70% of the world’s population of people living with HIV reside in sub-Saharan Africa, there are minimal prospective data on the contributions of HIV infection to atherosclerosis in the region. METHODS AND RESULTS: We conducted a prospective observational cohort study of people living with HIV on antiretroviral therapy >40 years of age in rural Uganda, along with population-based comparators not infected with HIV. We collected data on cardiovascular disease risk factors and carotid ultrasound measurements annually. We fitted linear mixed effects models, adjusted for cardiovascular disease risk factors, to estimate the association between HIV serostatus and progression of carotid intima media thickness (cIMT). We enrolled 155 people living with HIV and 154 individuals not infected with HIV and collected cIMT images at 1045 visits during a median of 4 annual visits per participant (interquartile range 3–4, range 1–5). Age (median 50.9 years) and sex (49% female) were similar by HIV serostatus. At enrollment, there was no difference in mean cIMT by HIV serostatus (0.665 versus 0.680 mm, P=0.15). In multivariable models, increasing age, blood pressure, and non–high- density lipoprotein cholesterol were associated with greater cIMT (P<0.05), however change in cIMT per year was also no different by HIV serostatus (0.004 mm/year for HIV negative [95% CI, 0.001–0.007 mm], 0.006 mm/year for people living with HIV [95% CI, 0.003–0.008 mm], HIV×time interaction P=0.25). CONCLUSIONS: In rural Uganda, treated HIV infection was not associated with faster cIMT progression. These results do not support classification of treated HIV infection as a risk factor for subclinical atherosclerosis progression in rural sub-Saharan Africa.
Keywords: Antiretroviral therapy; Atherosclerosis; Cardiovascular disease risk; Carotid intima media thickness; HIV infection; Uganda